Relasi musik dan spiritualitas: Kajian terhadap lirik lagu Dewa 19 - Saraswati, Widya Kirana (Maliki Interdisciplinary Journal, 2026)
This study examines the relationship between music and spirituality in the lyrics of the song “Satu” by Dewa 19 using a semiotic approach. The method employed is descriptive-analytical qualitative research, with the song lyrics serving as the primary data. The analysis draws on Roland Barthes’s theory of semiotics, which distinguishes between denotative and connotative meanings. The results of the study indicate that, in terms of direct meaning, the song’s lyrics depict human awareness of God as the sole source of life. Meanwhile, on a deeper level, the lyrics reflect spiritual values such as tauhid—the belief in the oneness of God and the inner connection between humanity and Him. Some lyrics depict spiritual closeness, a sense of surrender, and the search for the meaning of life. Furthermore, the combination of simple yet poetic lyrics with an emotional melody enables this song to provide a touching and reflective experience for listeners. From these results, it can be concluded that popular music serves not only as entertainment but also as a medium for conveying spiritual messages and aiding the process of reflection in modern life.